Monitoring Study Participants and Implementation with Phone Calls to Support Hypertension Control During the COVID-19 Pandemic: The Case of a Multicomponent Intervention Trial in Guatemala - Diego Hernández-Galdamez; Kristyne Mansilla; Ana Lucía Peralta; Javier Rodríguez-Szaszdi; Juan Manuel Ramírez; Dina Roche; Pablo Gulayin; Manuel Ramirez-Zea; Jiang He; Vilma Irazola; Meredith P. Fort (Ubiquity Press, 2021)
Background: The COVID-19 pandemic presents a challenge to health care for patients with chronic diseases, especially hypertension, because of the important association and increased risk of these patients with a severe presentation of COVID-19 disease. The Guatemalan Ministry of Health has been implementing a multi-component program aimed at improving hypertension control in rural communities since 2019 as a part of an intervention research cluster randomized trial. When the first cases of COVID-19 were reported (March 13, 2020) in Guatemala, our study paused all study field activities, and began monitoring participants through phone calls. The objective of this paper is to describe the approach used to monitor study participants during the COVID-19 pandemic and compare data obtained during phone calls for intervention and control group participants. Methods: We developed a cross-sectional study within the HyTREC (Hypertension Outcomes for T4 Research within Lower Middle-Income Countries) project 'Multicomponent Intervention to Improve Hypertension Control in Central America: Guatemala' in which phone calls were made to participants from both intervention and control groups to monitor measures important to the study: delivery of antihypertensive medications in both groups, receipt of coaching sessions and use of a home blood pressure monitor by intervention group participants, as well as reasons that they were not implemented. Results: Regarding the delivery of antihypertensive drugs by the MoH to participants, those in the intervention group had a higher level of medication delivery (73%) than the control group (51%), p<0.001. Of the total participants in the intervention group, 62% had received at least one health coaching session in the previous three months and 81% used a digital home blood pressure monitor at least twice a week. Intervention activities were lower than expected due to restricted public transportation on top of decreased availability of health providers. Conclusion: In Guatemala, specifically in rural settings, access to antihypertensive medications and health services during pandemic times was impaired and less than expected, even after accounting for the program's implementation activities and actions.